P822 Impact of extra-intestinal manifestations at diagnosis on disease outcome in paediatric- and elderly-onset Crohn′s Disease: A French population-based study. (16th January 2018) - Duricová, D; Sarter, H; Savoye, G; Leroyer, A; Pariente, B; Armengol-Debeir, L; Bouguen, G; Ley, D; Turck, D; Templier, C; Buche, S; Peyrin-Biroulet, L; et al.
Abstract: Background: An association between extraintestinal manifestations (EIM) and more serious disease outcome has been reported. The aim of this study was to assess the occurrence of EIM in paediatric- and elderly-onset Crohn's disease (CD); the factors associated with EIM and their impact on long-term disease outcome. Methods: Paediatric (<17 years at diagnosis) and elderly-onset CD patients (≥60 years at diagnosis) from a prospective population-based registry (EPIMAD) were included. Data on EIM and clinical factors at diagnosis and maximal follow-up were collected. Results: Five hundred Thirty-five paediatric- and 370 elderly-onset patients were included (median age 14.5 and 69.9 years; median follow-up 11.1 and 5.9 years). EIM occurred in 23.5% of childhood- and 4.9% of elderly-onset patients at diagnosis while 29.8% and 5.9% of individuals developed new EIM during the disease course (HR 4.4, 95% CI: 2.7–7.0, p < 0.001). The most frequently affected organ in both cohorts, either at diagnosis or during follow-up, were joints (paediatric: 11.2% and 22.3%; elderly: 3.2% and 3.5%, respectively) followed by skin (paediatric: 15.9% and 13.2%; elderly: 2.7% and 2.7%, respectively). The presence of EIM at diagnosis increased the risk for corticosteroids (HR 1.42, 95% CI 1.14–1.78 and HR 3.38, 95% CI: 1.88–6.08) and immunosuppressants (HR 1.30, 95% CI: 1.02–1.65 and HR 4.24, 95% CI: 1.91–9.42) both in paediatrics and elderly. In contrast, paediatric-onset patients with EIM at diagnosis seemed to have lower risk of intestinal surgery (HR 0.73, 95% CI: 0.53–1.02) but this result did not reach statistical significance ( p = 0.06). Conclusions: Age at diagnosis had significant impact on EIM presentation with low occurrence in elderly- compared with paediatric-onset patients. EIM at diagnosis was independent predictor of need for corticosteroids and immunosuppressants in both age cohorts while paediatric-onset individuals with EIM had a trend to lower risk of bowel surgery.